DISCHARGES OF NATURAL RADIONUCLIDES INTO THE ENVIRONMENT DUE TO FUNCTIONING OF THE ENTERPRISES OF NON-NUCLEAR INDUSTRIES - E. P. Lisachenko; I. P. Stamat; A. L. Zeldin (Радиационная гигиена)
In the present overview we analyze the literary data concerning discharges of natural radionuclides into the environment due to functioning of the enterprises of non-nuclear industries. We consider their quantitative characteristics of discharges, the peculiarities of the formation of radionuclide composition of discharges from various industrial branches, the information about the population exposure doses due to these discharges, as well as the possibilities of standardization of the industrial discharges of natural radionuclides.